Genetic predictors of chemotherapy-related amenorrhea in women with breast cancer - Ruddy, Kathryn J.; Schaid, Daniel J.; Partridge, A. H.; Larson, Nicholas B.; Batzler, Anthony; Häberle, Lothar; Dittrich, Ralf; Widschwendter, P.; Fink, Visnja; Bauer, Emanuel; Schwitulla, Judith; Rübner, Matthias; et al. (Fertility and Sterility, 2019)
Objective: To study how genetics may play a role in determining risk of chemotherapy-related amenorrhea (CRA) in young women with breast cancer. Design: Genome-wide association study. Setting: Not applicable. Patient(s): Premenopausal women ≤45 years of age enrolled in one of these three trials were included if they had at least one menstrual case report form after chemotherapy ended and if they were of European ancestry. Forms during and up to 3 months after receipt of GnRH agonist were excluded. Intervention(s): None. Main Outcome Measure(s): The association of single-nucleotide polymorphisms with post-chemotherapy menstruation adjusted for trial and arm, age, tamoxifen use, and nodal status. Result(s): The median age of the 1,168 women was 41 years (range 19–45). Among these, 457 (39%) never resumed menses after chemotherapy. Older age, tamoxifen use, and node-negative disease were associated with increased risk of CRA. Adjusting for these, rs147451859, in an intron of PPCDC (phosphopantothenoylcysteine decarboxylase), and rs17587029, located 5′ upstream of RPS20P11 (ribosomal protein S20 pseudogene 11), were associated with post-chemotherapy menstruation. Conclusion(s): Genetic variation may contribute to risk of CRA. Better prediction of who will experience CRA may inform reproductive and treatment decision making in young women with cancer.
CRIS-Team Scopus Importer:2019-08-06
Keywords: amenorrhea; Breast neoplasms; drug therapy; toxicity